(untitled) (Ingenio Magno, 2018)
The dynamic analysis of engineering works represents a significant tool to evaluate the behavior of these against seismic events and provide useful quantitative results in making timely decisions. Therefore, it is required that the seismic signals or accelerograms to be used in these analyzes represent in the most accurate way the expected ground movements that can affect the behavior of structures mentioned above. This article focuses on describing the methodology and criteria used for the search and selection of accelerogramas recorded in the national database of seismic events of the RNAC Red Nacional de acelerógrafos, as well as in the database of international simian events - PEER (Ground Motion Database). Additionally, the results of the processing of the selected accelerogramas that will be used in the dynamic analysis of the Teatine Dam are presented, based on the results obtained from the seismic hazard analysis carried out. The objective is to obtain response spectra that resemble the uniform threat spectrum for a return period T = 475 years corresponding to the maximum probable earthquake S.M.P. Three representative seismic records were selected from each of the most influential seismogenic sources, that is, three accelerogramas from a nearby source, three from an intermediate source and three from a distant source.